THE INDEX EFFECT - IS IT POSSIBLE TO PREDICT? - Tavor, Tchai (Journal of Advanced Studies in Finance, 2011)
The stock index is the basis for the existence of index instruments, such as ETFs and index funds. Therefore, every event in the index is a significant event which has many implications in the investment world. An important event is the index update which occurs every six months. The update of the indexes redefines the companies which are dropped or entered to the list and it consequently determines the future of the stocks, for good or for worse. This article examines the phenomenon of the Index Effect in the Israeli market using the Event Studies approach from a different angle. The analysis will be done on the period prior to the announcement day of the index entry, on the announcement day and during the period following the announcement day. The study tries to characterize the phenomenon by using two tests: Industry sectors and month of entry. The outcome of the study indicates a difference between the groups in both tests. The first test shows that the market responds stronger to the high-tech companies than to the rest of the market sectors. The second test shows that stock returns of companies entering the index in the month of January are higher than those which enter in July.